Pulmonary Large Cell Neuroendocrine Carcinoma Associated With Lambert-Eaton Syndrome - Pamela Hernandez-Arriaga; Mauricio Gonzalez-Urquijo; Daniel Fernando López Altamirano; Bryan Vaca-Cartagena; Andres Vergil-Vargas; Silviano Rios-Pascual; Jose Eduardo Perez-Saucedo; Ricardo Sepúlveda-Malec (SAGE Publishing, 2021)
Lambert-Eaton syndrome is a rare paraneoplastic disorder of the neuromuscular junction, characterized by impaired release of acetylcholine, which causes proximal muscle weakness, depressed tendon reflexes, and autonomic changes. Most cases of Lambert-Eaton syndrome present in small-cell lung carcinoma, and only a few cases have been reported in other lung subtypes. Herein, we report a case of 69 years old male patient with Lambert-Eaton syndrome as a rare association with a pulmonary large-cell neuroendocrine carcinoma, which presented 5 months before neoplasm diagnosis. A lobectomy was auspiciously performed. A review of the literature is also presented.